Zootechnical characterization of the lizard Callopistes flavipunctatus de Morrope - Arbulú López, César Augusto (2018)
This study to characterize zootechnically to the lizard C. flavipunctatus as a food source and natural resource cooperating for its preservation and sustainable exploitation was done. From January to April 2015, in the countryside Mórrope specimen of both sexes was collected, in which the body weight, weight and carcass yield, acceptance of meat flavor was evaluated. The results indicate that the lizard evaluated should be considered as a quality meat suitable source. It is suggest to continue with the investigation of the species to determine if any real effect on the qualities assumed by popular culture, rule out the presentation of zoonoses and the possibility to create protected or exclusion zones to allow the best reproduction of the species to avoid predation and repopulate the forest.  Key words: Zootechnical characterization, lizard, Callopistes flavipunctatus.